Productive performance of Holstein and the crossbreding Kiwi Cross x Holstein cattle = Rendimiento productivo de Ganado Holstein y el cruzamiento Kiwi Cross x Holstein - Mogollón García, Henry David; Nieto Sierra, David Felipe; Castro Rincón, Edwin (2020)
Introduction. During decades, milk production in the department of Nariño has depended on the Holstein breed. For this reason, it is necessary to evaluate a model of milk production that allows to decrease production costs and in turn improves the compositional quality of the milk. Objective. This study aimed was to compare the monthly milk production, days in lactation (DIM), and milk production per third of lactation of the F1 crossing of the Kiwi Cross (KC) and Holstein (HO) breeds, under grazing conditions in the high tropics of the Nariño department, Colombia. Materials and methods. Monthly milk production in HO cows (n=30) and F1 (n=40) was measured by adjusting the DIM, milk production was also obtained by third of lactation, fat, protein, and total solids. Results. Maximum production was higher for HO cows compared to KC (25.8±0.53 vs. 23.2±0.53 l day-1) (p<0.05). Production per third of lactation was higher (p<0.05) in the first third compared to the second and third periods for both breeds study (HO: 13.6±0.56 vs.11.3±0.5723 and 9.9±0.47 l day-1, and KC: 12.8±0.4505 vs. 10.6±0.66 and 9.5±1.69 l day-1). Fat was higher (p<0.05) in Kiwi Cross F1 crosses than in Holstein, at weeks one, three, and five (4±0.07, 4±0.07, 4±0.07 vs. 3.6±0.12, 3.6±0.11, 3.7±0.09 %, respectively); likewise, protein in weeks one and four was higher in the KC group compared to HO (3.3±0.04 vs. 3.1±0.05 %; p<0.05). Total solids were 13.3±0.17 vs. 12.5±0.23 % (p<0.05) for F1 and HO cows, respectively at weeks two and five. Conclusion. F1 and Holstein (HO) milk production was similar; however, KC improved the performance in the compositional milk quality, increasing the percentages of fat, protein, and total solids.
Introducción. Durante décadas la producción de leche en el departamento de Nariño ha dependido de la raza Holstein. Por ello, se hace necesario evaluar un modelo de producción lechera que permita disminuir costos de producción y a su vez mejore la calidad composicional de la leche. Objetivo. El objetivo de este estudio fue comparar la producción mensual de leche, días en lactación (DIM) y la producción de leche por tercio de lactancia del cruce F1 de las razas Kiwi Cross (KC) y Holstein (HO), en condiciones de pastoreo en los trópicos altos del departamento de Nariño, Colombia. Material y métodos. La producción mensual de leche en vacas HO (n=30) y F1 (n=40) se midió ajustando la DIM, también se obtuvo la producción de leche por tercio de la lactancia, grasa, proteína y sólidos totales. Resultados. La producción máxima fue mayor para vacas HO comparado con KC (25,8±0,53 vs. 23,2±0,53 l día-1). La producción por tercio de lactancia fue mayor en el primer tercio comparado con el segundo y tercero (HO: 13,6±0,56 vs 11,3±0,5723 y 9,9±0,47 l día-1, y KC: 12,8±0,4505 vs 10,6±0,66 y 9,5±1,69 l día-1). La grasa fue mayor (p<0,05) en los cruces F1 de Kiwi Cross que en Holstein, en las semanas uno, tres y cinco (4±0,07; 4±0,07; 4±0,07 vs 3,6±0,12; 3,6±0,11; 3,7±0,09 %, respectivamente). La proteína en las semanas uno y cuatro fue mayor en el grupo KC frente a HO (3,3±0,04 vs 3,1±0,05 %; p<0,05). Sólidos totales fueron de 13,3±0,17 vs 12,5±0,23 % para las vacas F1 y HO, respectivamente, en las semanas dos y cinco. Conclusión. La producción de leche de la F1 y de Holstein (HO) fue similar; sin embargo, KC mejoró el rendimiento en la calidad composicional de la leche, y aumentó los porcentajes de grasa, proteína y sólidos totales.
En Revista Agronomía mesoamericana
Volumen 31, número 2 (mayo-agosto 2020)
Descripción basada en el contenido visto el 21 de agosto, 2023
También disponible en formatos EPUB, HTML y XML
Keywords: LECHE -- PRODUCCION -- INVESTIGACIONES; LECHE -- CALIDAD -- EVALUACION; GANADO HOLSTEIN-FRIESIAN